Factors Influencing Occupational Stress of State Security Forces During the COVID-19 Pandemic: A Scoping Review - García-Iglesias JJ; Chirico F; Rizzo A; Szarpak L; Khabbache H; Yildirim M; Fagundo-Rivera J; Gómez-Salgado J (Dove Medical Press, 2024)
Juan Jesús García-Iglesias,1 Francesco Chirico,2,3 Amelia Rizzo,4,5 Lukasz Szarpak,6,7 Hicham Khabbache,8,9 Murat Yildirim,10- 12 Javier Fagundo-Rivera,13 Juan Gómez-Salgado1,14 1Department of Sociology, Social Work and Public Health, Faculty of Labour Sciences, University of Huelva, Huelva, Spain; 2Post-Graduate School of Occupational Health, Catholic University of the Sacred Heart, Rome, Italy; 3Health Service Department, Italian State Police, Ministry of the Interior, Milan, Italy; 4Department of Clinical and Experimental Medicine, University of Messina, Messina, Italy; 5Department of Cognitive Sciences, Psychological, Educational, and Cultural Studies, University of Messina, Messina, Italy; 6Department of Clinical Research and Development, LUXMED Group, Warsaw, Poland; 7Centre for Development, Commercialisation and Technology Transfer, Collegium Medicum, The John Paul II Catholic University of Lublin, Lublin, Poland; 8Director of the UNESCO Chair "Lifelong Learning Observatory" (UNESCO/UMSBA), Rabat, Morocco; 9Department of Psychology, Laboratory of «Morocco: History, Theology and Languages», Faculty of Arts and Human Sciences Fès-Saïss, Sidi Mohamed Ben Abdellah University, Fez, Morocco; 10Department of Psychology, Faculty of Science and Letters, Agri Ibrahim Cecen University, Ağrı, Türkiye; 11Department of Social and Educational Sciences, Lebanese American University, Beirut, Lebanon; 12Department of Psychology, School of Humanities, Education and Social Sciences, Khazar University, Baku, Azerbaijan; 13Centro Universitario de Enfermería Cruz Roja, Sevilla, Spain; 14Safety and Health Postgraduate Programme, University of Espíritu Santo, Guayaquil, EcuadorCorrespondence: Juan Gómez-Salgado, Department of Sociology, Social Work and Public Health, Faculty of Labour Sciences, University of Huelva, Avda. Tres de Marzo, Huelva, S/N, 21007, Spain, Tel +34 959219700, Email salgado@uhu.es Javier Fagundo-Rivera, Centro Universitario de Enfermería Cruz Roja, Avda. de la Cruz Roja, 1, duplicado, Sevilla, 41009, Spain, Tel +34 954350997, Email javier.fagundo@cruzroja.esObjective: The aim of this review was to assess the factors influencing the occupational stress of state security forces during the COVID-19 pandemic.Methods: We conducted a scoping review using the Pubmed, Scopus, and Web of Science databases, adhering to the PRISMA statement standards and the guidelines for narrative syntheses.Results: We included a total of 26 studies. The prevalence of stress varied from 22% to 87.2%. Factors that may have influenced the stress levels of police officers during the pandemic include not having basic personal protective equipment, having little or no rest periods between tasks, long working hours, fear of contagion to themselves or others, pressure to maintain law and order, emotion regulation and preparedness, sex, marital status, work experience, age, presence of chronic underlying illnesses, family-work conflict, lack of psychological support, and others. The long working hours, the fear of infecting themselves or others, the pressure to maintain law and order, sex, and age are the six main factors evaluated for more studies.Conclusion: Organisational, situational, and personal factors may have influenced the stress levels of police officers during the pandemic, and measures need to be taken to minimise their impact.Keywords: COVID-19, police, state security forces, stress, occupational health